Spatialtemporal shifts of ponyfish (Perciformes: Leiognathidae) diversity in by_catch of trawl fishery, including morph variation of Photopectoralis bindus - Wanlada Klangnurak; James D. True (My University, 2021)
Ponyfish (Perciformes: Leiognathidae) are a diverse group of mainly small, planktivorous fishes that comprise much of the teleost component found in the by-catch of trawlers in Thai waters. The generic taxonomy of ponyfish has been revised many times, which has resulted in confusion in the historical records of fishing data. Moreover, since two monsoon seasons affect the different coasts of Thailand at different times of the year, their effects are likely to have separate impacts on marine fish diversity in Thailand according to the time of year. By-catch samples totaling 25,439 ponyfish were collected from commercial fishing vessels during three sampling episodes in each of two Andaman Sea provinces and three provinces in the Gulf of Thailand. Ponyfish samples were identified to the species level and taxonomical ambiguity was dealt with by DNA sequencing against GenBank to identify the specie. From these data, the spatial and temporal community diversity and abundance were calculated. Richness and total abundance were significantly different between seasons but not between the two sides of the Thai peninsula. Diversity of ponyfish in bycatch was least during the monsoon transition period or the dry season. Morphological variation of Photopectoralis bindus has been a source of taxonomic confusion in the past, but here, the use of DNA sequencing in addition to body ratio data analysis reinforces taxonomic clarity and suggests population-level structuring that may explain these issues. These findings indicate the role of seasonal fluctuations in biodiversity maintenance for fisheries management in Thailand.
Keywords: Perciformes; Variation (astronomy); Identification and Quantification in Food